Composite trigonometry gone complex!

Algebra Level 3

If sin ( cos x ) = a + i b \sin(\cos x) = a+ib , where a a and b b are real and i = 1 i = \sqrt{-1} is the imaginary unit , then

x = π s 1 c 2 s 1 π + i ( ln s 1 ln ( t ± t s 1 s 2 ) ) x = - \frac \pi{s_1} - c_2s_1 \pi + i\left(\ln s_1 - \ln\left(t \pm \sqrt{t^{s_1}-s_2} \right)\right)

where t = ( c 1 s 2 + s 3 ) π + i s 1 ln ( b + i a ± s 3 ( a + i b ) s 1 ) t = (c_1s_2+s_3)\pi + i s_1\ln \left(-b+ia \pm \sqrt{s_3-(a+ib)^{s_1}} \right) with c 1 c_1 and c 2 c_2 being integers and s 1 s_1 , s 2 s_2 , and s 3 s_3 , positive integers less than 5 5 .

Find s 1 + s 2 + s 3 s_1 + s_2 + s_3 .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

James Watson
Aug 4, 2020

We need to use the complex expressions of sine and cosine .

Let cos ( x ) = u \cos(x) = u first so that we can deal with the sine on its own. sin ( u ) = a + b i \sin(u) = a+bi e i u e i u 2 i = a + b i \Longrightarrow \frac{e^{iu}-e^{-iu}}{2i}=a+bi e i u e i u = 2 i ( a + b i ) = 2 b + 2 a i \Longrightarrow e^{iu}-e^{-iu} = 2i(a+bi) = -2b + 2ai ( e i u ) 2 1 = ( 2 b + 2 a i ) e i u ( e i u ) 2 ( 2 b + 2 a i ) e i u 1 = 0 \Longrightarrow (e^{iu})^2 - 1 = (-2b+2ai)e^{iu} \Longrightarrow (e^{iu})^2 - (-2b+2ai)e^{iu}-1=0

We can use the quadratic formula here to find e i u e^{iu} : ( e i u ) 2 ( 2 b + 2 a i ) e i u 1 = 0 (e^{iu})^2 - (-2b+2ai)e^{iu}-1=0 e i u = ( 2 b + 2 a i ) ± ( 2 b + 2 a i ) 2 4 ( 1 ) ( 1 ) 2 ( 1 ) = 2 b 2 a i ± 2 1 ( a + b i ) 2 2 = b a i ± 1 ( a + b i ) 2 \begin{aligned} \Longrightarrow e^{iu} &= \frac{-(-2b+2ai) \pm \sqrt{(-2b+2ai)^2 - 4(1)(-1)}}{2(1)} \\ &= \frac{2b-2ai \pm 2\sqrt{1-(a+bi)^2}}{2} = b-ai\pm \sqrt{1-(a+bi)^2} \end{aligned} i u = ln ( b a i ± 1 ( a + b i ) 2 ) = ln ( a i b ± 1 ( a + b i ) 2 ) + ln ( 1 ) = ln ( a i b ± 1 ( a + b i ) 2 ) + π i 2 + 2 π i C 1 \begin{aligned} \Longrightarrow iu = \ln(b-ai\pm \sqrt{1-(a+bi)^2}) &= \ln(ai-b\pm \sqrt{1-(a+bi)^2}) + \ln(-1) \\ &= \ln(ai-b\pm \sqrt{1-(a+bi)^2}) + \frac{\pi i}{2}+2\pi iC_1 \end{aligned}

Note: ln ( 1 ) = ln ( e π 2 i + 2 π n i ) = π i 2 + 2 π n i \ln(-1) = \ln(e^{\frac{\pi}{2}i + 2\pi ni}) = \cfrac{\pi i}{2} + 2\pi ni where n n is an integer.

u = ln ( a i b ± 1 ( a + b i ) 2 ) i π 2 2 π C 1 \Longrightarrow u = - \ln(ai-b\pm \sqrt{1-(a+bi)^2}) i - \frac{\pi}{2} - 2\pi C_1

We can now sub in cos ( x ) \cos(x) and use the complex expression of cosine now: cos ( x ) = ln ( a i b ± 1 ( a + b i ) 2 ) i π 2 2 π C 1 \Longrightarrow \cos(x) = - \ln(ai-b\pm \sqrt{1-(a+bi)^2}) i - \frac{\pi}{2} - 2\pi C_1 e i x + e i x 2 = ln ( a i b ± 1 ( a + b i ) 2 ) i π 2 2 π C 1 \Longrightarrow \frac{e^{ix}+e^{-ix}}{2} = - \ln(ai-b\pm \sqrt{1-(a+bi)^2}) i - \frac{\pi}{2} - 2\pi C_1 e i x + e i x = 2 ln ( a i b ± 1 ( a + b i ) 2 ) i π 4 π C 1 \Longrightarrow e^{ix}+e^{-ix} = - 2\ln(ai-b\pm \sqrt{1-(a+bi)^2}) i - \pi - 4\pi C_1 ( e i x ) 2 + = [ 2 ln ( a i b ± 1 ( a + b i ) 2 ) i + π + 4 π C 1 ] e i x \Longrightarrow (e^{ix})^2 + = -\left[ 2\ln(ai-b\pm \sqrt{1-(a+bi)^2}) i + \pi + 4\pi C_1 \right] e^{ix}

We can let t = 2 ln ( a i b ± 1 ( a + b i ) 2 ) i + π + 4 π C 1 t = 2\ln(ai-b\pm \sqrt{1-(a+bi)^2}) i + \pi + 4\pi C_1 to save the writing: ( e i x ) 2 + 1 = t e i x \Longrightarrow (e^{ix})^2 + 1 = -t e^{ix} ( e i x ) 2 + t e i x + 1 = 0 \Longrightarrow (e^{ix})^2 + te^{ix} + 1 = 0

We can now solve for e i x e^{ix} using the quadratic formula once again: e i x = ( t ) ± ( t ) 2 4 ( 1 ) ( 1 ) 2 ( 1 ) = t ± t 2 4 2 \begin{aligned} \Longrightarrow e^{ix} &= \frac{-(t) \pm \sqrt{(-t)^2 - 4(1)(1)}}{2(1)} \\ &= \frac{-t \pm \sqrt{t^2 - 4}}{2} \end{aligned} i x = ln ( t ± t 2 4 2 ) = ln ( t ± t 2 4 ) + ln ( 1 ) ln ( 2 ) = ln ( t ± t 2 4 ) ln ( 2 ) + π i 2 + 2 π i C 2 \begin{aligned} \Longrightarrow ix = \ln \left(\frac{-t \pm \sqrt{t^2 - 4}}{2} \right) &= \ln(t \pm \sqrt{t^2 - 4}) + \ln(-1) - \ln(2) \\ &= \ln(t \pm \sqrt{t^2 - 4}) - \ln(2) + \frac{\pi i}{2} + 2\pi iC_2 \end{aligned} x = ln ( 2 ) i ln ( t ± t 2 4 ) i π 2 2 π C 2 \Longrightarrow x = \ln(2)i - \ln(t \pm \sqrt{t^2 - 4})i - \frac{\pi}{2} - 2\pi C_2

Thus, we get x x as π 2 2 π c 2 + i ( ln ( 2 ) ln ( t ± t 2 4 ) ) \boxed{ - \frac{\pi}{ \blue{2} } - \blue{2} \pi c_2 + i(\ln(\blue{2}) - \ln(t \pm \sqrt{t^\blue{2} - \red{4}})) } where t = ( c 1 4 + 1 ) π + i 2 ln ( a i b ± 1 ( a + b i ) 2 ) \boxed{ t = (c_1 \red{4}+\green{1}) \pi + i\blue{2}\ln(ai-b\pm \sqrt{\green{1}-(a+bi)^\blue{2}})}

We can deduce that s 1 = 2 , s 2 = 4 \blue{s_1} = \blue{2}, \red{s_2} = \red{4} and s 3 = 1 \green{s_3} = \green{1} so: n = 1 3 s n = 2 + 4 + 1 = 7 \large \sum_{n=1}^{3}s_n = \blue{2}+\red{4}+\green{1} = \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...